2018
DOI: 10.1111/eci.12960
|View full text |Cite
|
Sign up to set email alerts
|

Homoarginine and all‐cause mortality: A systematic review and meta‐analysis

Abstract: This meta-analysis of observational studies showed an inverse association between circulating homoarginine concentrations and all-cause mortality. Further research is warranted to investigate the direct effects of homoarginine on cardiovascular homoeostasis, the associations between homoarginine and all-cause mortality in other population groups, and the effects of interventions on homoarginine concentrations on clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Most consistently, low hArg levels are associated with all-cause and cardiovascular mortality, which was shown in subjects referred for coronary angiography, in hemodialysis patients with diabetes mellitus, in stroke patients, but also population-based cohorts [89,[91][92][93][94]. A recent meta-analysis confirmed the inverse association of hArg with all-cause mortality (HR 0.64 [0.57-0.73]) [95]. More specifically, low hArg levels were strongly associated with fatal strokes and revealed a trend to increase stroke risk [96,97].…”
Section: Homoarginine As Marker and Target In Cerebrovascular Diseasesmentioning
confidence: 83%
“…Most consistently, low hArg levels are associated with all-cause and cardiovascular mortality, which was shown in subjects referred for coronary angiography, in hemodialysis patients with diabetes mellitus, in stroke patients, but also population-based cohorts [89,[91][92][93][94]. A recent meta-analysis confirmed the inverse association of hArg with all-cause mortality (HR 0.64 [0.57-0.73]) [95]. More specifically, low hArg levels were strongly associated with fatal strokes and revealed a trend to increase stroke risk [96,97].…”
Section: Homoarginine As Marker and Target In Cerebrovascular Diseasesmentioning
confidence: 83%
“…Results from several previous studies in patients with prevalent CVD showed an association between low homoarginine plasma concentrations and a higher risk of CVD (i.e., sudden cardiac death, heart failure, and myocardial infarction), cerebrovascular outcomes, and mortality (both all-cause and CVD-related) [1][2][3][4][5]. In the present investigation, we confirmed the association of homoarginine with all-cause mortality in a large community-based sample that included few people with prevalent CVD, and we extended our analyses to also include CRP, BNP, GDF15, eGFR, and troponin I as covariates.…”
Section: Homoarginine In the Communitymentioning
confidence: 99%
“…Clinical evidence suggests that lower circulating homoarginine concentrations are a risk factor for cardiovascular disease, and all-cause mortality [1,2]. Patients with prevalent ischemic stroke, ischemic heart disease, and congestive heart failure have low blood homoarginine concentrations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…52 Recent studies reported low L-homoarginine concentrations to be a risk marker for cardiovascular events and all-cause mortality in the general population and coronary heart disease as well as kidney disease patients. 52,53 So, supplementation with L-homoarginine and L-arginine derivatives (and others selected pharmaceutical supplements), dietary beneficial habits, intake of antioxidant and anti-inflammatory foods and balanced physical activity improved endothelium function. 9,51 At a pathological environment, the endothelium assembly (arrangement of a proatherosclerotic structure) and function (deficit of guarding role) are altered, leading to endothelium dysfunction.…”
Section: On Endothelium Remodelingmentioning
confidence: 99%